A Robust Numerical Method for Generalized Coulomb and Self-Polarization Potentials of Dielectric Spheroids (Communications in Computational Physics, 2010)
By utilizing a novel quasi-harmonic three-layer dielectric model for theinterface between a dielectric spheroid and the surrounding dissimilar dielectricmedium, a robust numerical method for calculating the generalized Coulomb andself-polarization potentials of the dielectric spheroid is presented in this paper. Theproposed numerical method can not only overcome the inherent mathematical divergencein the self-polarization energy which arises for the simplest step-like model ofthe dielectric interface, but also completely eliminate the potential numerical divergencewhich may occur in other treatments. Numerical experiments have demonstratedthe convergence of the proposed numerical method as the number of the stepsused to discretize the translation layer in a general three-layer dielectric model goes toinfinity.